2013
DOI: 10.1111/ctr.12079
|View full text |Cite
|
Sign up to set email alerts
|

Combination of pulse methylprednisolone infusions with cyclosporine‐based immunosuppression is safe and effective to treat recurrent focal segmental glomerulosclerosis after pediatric kidney transplantation

Abstract: MP infusion therapy in combination with CsA-based immunosuppression could be safe and effective in treating recurrent FSGS after kidney transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Since management of FSGS recurrence remains largely anecdotal due to the absence of multicentered controlled studies, most centers, use variable regimens, which include plasmapheresis in combination with pulse steroids, cyclophosphamide, high-dose cyclosporine or rituximab. 1,[27][28][29][30] The use of IA is superior to plasmapheresis, in terms of adverse events and the need for substitutive interventions afterwards. Plasmapheresis is a nonselective aphaeretic procedure, and preservation of several essential plasma components including albumin, immunoglobulins and clotting factors is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Since management of FSGS recurrence remains largely anecdotal due to the absence of multicentered controlled studies, most centers, use variable regimens, which include plasmapheresis in combination with pulse steroids, cyclophosphamide, high-dose cyclosporine or rituximab. 1,[27][28][29][30] The use of IA is superior to plasmapheresis, in terms of adverse events and the need for substitutive interventions afterwards. Plasmapheresis is a nonselective aphaeretic procedure, and preservation of several essential plasma components including albumin, immunoglobulins and clotting factors is not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the paper by Canaud et al [33] , who described a combined treatment of CyA in association with high dose steroids and PE, Shishido et al [41] also reported a favorable outcome (7/10 complete remission) for pediatric patients with FSGS recurrence in response to a combined treatment with methylprednisolone pulses (20 mg/kg after diagnosis on 3 consecutive days in weeks 1, 3 and 5) and an increase in CyA target levels (area under the curve0-4 4500-5500 ng/h per milliliter for the first month, 4000 ng/h per milliliter for the next 2 mo, and 3000 ng/h per milliliter thereafter).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Canaud et al [33] described positive outcome (complete remission at 3 mo after diagnosis) for 10 patients with FSGS recurrence that had been treated with a 9-mo course of intravenous cyclosporine (CyA; C0 levels at 200-400 ng/mL), followed by oral CyA (C2 levels at 1200-1400 ng/mL), high dose oral steroids (1 mg/kg per day for the first 4 wk, then progressively tapered) and a course of PE sessions. The only patient who experienced recurrence of [33] 10 patients Gohh et al [31] Prophylactic course of 8 PE sessions in the peri-operative period in patients at high risk of recurrence 10 patients (1 < 18 yr, 9 ≥ 18 yr) 7/10 free of recurrence Chikamoto et al [32] Prophylactic course of 4 PE sessions 12 [41] Methylprednisolone pulses (20 mg/kg on three consecutive days in weeks 1, 3 and 5) and increasing CyA target levels 10 patients (8 < 18 yr, 2 ≥ 18 yr)…”
Section: Plasma Exchangementioning
confidence: 99%
“…As a result, there is interest in the use of other treatments that intensify immunosuppression, notably plasmapheresis and biological antibodies (e.g., rituximab), often coupled with pulse corticosteroids and calcineurin inhibitors. Recent reports indicate that up to 70 % of pediatric patients with recurrent FSGS can achieve a complete remission and stabilization of kidney function for up to 10 years in response to a combination of cyclosporine and pulse intravenous methylprednisolone [45]. Drugs that interfere with the renin-angiotensin axis and a calcineurin inhibitor may be added to the therapeutic regimen in patients who fail to respond adequately to plasma exchange or rituximab.…”
Section: Treatmentmentioning
confidence: 99%